Interaction of Compliance Pressure, Task Complexity, and Auditor Experience on Audit Judgment Quality - Fakhirah, Sarah; Sutrisno, Sutrisno; Prihatiningtias, Yeney Widya (Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to examine the influence of compliance pressure and task complexity on audit judgment, as well as analyze the moderating role of audit experience in these relationships. The research was conducted on auditors working at Big Ten Public Accounting Firms in Indonesia. This study uses a quantitative approach with a survey method by distributing structured questionnaires to 170 auditors in 2025 who were the respondents of this study. Data analysis was carried out to test the direct effects and the moderating variable. The results show that compliance pressure has a significant negative effect on audit judgment. This indicates that auditors under compliance pressure tend to make less independent or objective audit judgments. On the other hand, task complexity does not show a significant influence on audit judgment, suggesting that auditors are able to manage complexity through procedural or institutional support. Furthermore, audit experience does not moderate the relationship between either compliance pressure or task complexity and audit judgment.